Female Labour Force Participation Rates in Rural Pakistan: Some Fundamental Explanations and Policy Implications (The Pakistan Development Review, 1987)
Labour supply is a key element in socio-economic development, and although the size, growth and composition of population have a strong bearing on its supply in an economy, the actual labour supply is a function of the labour force participation rate defined as the ratio of the population engaged in or seeking gainful employment to the working-age population. In Pakistan gainful employment means not only work for pay or profit but also unpaid help from family members, and the working-age population refers to the group of those aged 10 years or more. Although the use of labour force for computing participation rates has been criticised on the ground that it lays undue emphasis on market activities which have little relevance tb the less developed countries, particularly to the rural sector, (Standing 1978), it is nonetheless useful in studying household decisions regarding allocation of available time between productive and non-productive activities (Rees 1973). It is basically this division of labour between productive and non-productive activities that sheds light on the degree of development of an economy and, therefore, on the organization of factors of production (Yotopoulos 1986). The significance of rural participation rates, especially those of females, is noteworthy in this regard as there is a positive association between female productive work and the level of development achieved (Denti 1968). Female participation rates are also important for a proper understanding of the productive and reproductive roles of the population. As more than 70 percent of rural population depends on agriculture for its livelihood and rural females are nearly half of the total, their participation rates may be of critical importance in determining the rates of saving, investment and productivity in agriculture. It may also be noted that availability of labour in agriculture is also a function of the ready availability of female labour, especially for such operations as are performed exclusively by females, e.g. cotton picking.